THE STUDENTS’ VIEW OF THE FUNCTIONS OF MOTHER TONGUE IN GENERAL ENGLISH PROGRAM OF ABC COURSE - Magdalena Rolanda; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
This study aimed to find out the students ‘opinions on the use of mother tongue and its functions in Indonesian EFL classrooms. The data were the interviews with a total six students from level 1, 2 and 3 comprising one high achiever student and one low achiever student from each level. The findings show that all of the students agree that Indonesian can be occasionally used in the classroom by both teacher and students for a number of reasons: for the teacher to explain new and difficult vocabularies, explain grammar rules, organize tasks, maintain discipline, gain contact with individual students, for the students to ask and answer questions, communicate and discuss with classmates and for translating activities. The findings also show that the low proficiency students prefer to use Indonesian more than the higher proficiency students because of lack of vocabulary